Pharmacochemical Studies of Synthesized Coumarin–Isoxazole–Pyridine Hybrids - Matina D. Douka; Ioanna M. Sigala; Catherine Gabriel; Eleni Nikolakaki; Dimitra J. Hadjipavlou-Litina; Konstantinos E. Litinas (Molecules)
Several new coumarin–isoxazole–pyridine hybrids were synthesized through a 1,3-dipolar cycloaddition reaction of nitrile oxides, prepared in situ from pyridine aldehyde oximes, with propargyloxy- or propargylaminocoumarins in moderate-to-good yields. Synthetic modifications were applied using (diacetoxyiodo)benzene (PIDA) at room temperature, microwave irradiation, or tert-butyl nitrite (TBN) under reflux. Coumarin, isoxazole, and pyridine groups were selected for hybridization in one molecule due to their biological impact to inhibit lipid peroxidation and an enzyme implicated in inflammation. Preliminary in vitro screening tests for lipoxygenase (LOX) inhibition and anti-lipid peroxidation for the new hybrids were performed. A discussion on the structure–activity relationship is presented. Compounds 12b and 13a were found to be potent LOX inhibitors with IC50 5 μΜ and 10 μΜ, respectively, while 12b presented high (90.4%) anti-lipid peroxidation. Furthermore, hybrids 12b and 13a exhibited moderate-to-low anticancer activities on HeLa, HT-29, and H1437 cancer cells.